Human Factors Design Recommendation Optimisation: A process development for human-machine interface of the battery status on flight decks for electric regional aircrafts - Arosenius, Hedvig; Ivarsson, Sally (My University, 2023)
.The objective of this research is to investigate the integration of human factors in the development of a battery human-machine interface (HMI) for electric regional aircrafts. The study aims at examining how the integration of human factors can be improved in the development of novel features in the flight deck. Secondly, the study aims at analysing how the energy density of batteries compared to fuel affects the design considerations of the battery HMI for electric regional aircrafts. Lastly, the study is evaluating if low-fidelity prototyping is an effective way of validating the effectiveness of the process. The methodology used in this study is based on an interactive design process com bined with a product development process. The results were an implementation of a clear and structured process, which involves relevant stakeholders at each stage of development and utilises visual aids for better understanding, leads to effective collaboration and streamlined development. The final process design uses an ag ile approach with steps, iterative feedback-loops with each relevant department’s responsibilities clearly stated. Furthermore, the design of the battery HMI for elec tric regional aircrafts must take into account the lower energy density of batteries compared to fuel, which places a greater strain on pilots and the plane’s ability to estimate and supervise energy usage. Lastly, low-fidelity prototyping is an effective way of validating the process, as it highlights both the advantages and disadvantages of the early stages in the approach and identifies areas for improvement in a fast paced way.
Keywords: Human factors, Human-machine interface, Process development, Battery management, Aviation, Electric regional aircraft, Process optimisation.